2022
DOI: 10.1109/access.2022.3152525
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Design, Analysis and Experimental Validation of a High-Speed Permanent Magnet Synchronous Motor for Electric Turbocharger

Abstract: We developed a high-speed surface mounted permanent magnet synchronous motor (SPMSM) and a pulse width modulation (PWM)-driven inverter for a turbocharger with an additional electrically driven compressor (TEDC). These systems operate at 70,000 rpm and are intended to fit 1.6L diesel vehicles to reduce turbo lag to within 0.4 sec. There are key issues in the design of rotors for SPM type machines. To prevent the PM from scattering during high-speed operation, a retaining sleeve is necessary in the rotor. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In [14] also presented a high-speed rotor design with metallic and CFRP material. Based on results obtained from rotor dynamics analysis, it has been concluded that the CFRP retention sleeve has a better performance compared with metallic ones.…”
Section: Design Processmentioning
confidence: 99%
“…In [14] also presented a high-speed rotor design with metallic and CFRP material. Based on results obtained from rotor dynamics analysis, it has been concluded that the CFRP retention sleeve has a better performance compared with metallic ones.…”
Section: Design Processmentioning
confidence: 99%
“…PM materials feature high compressive strength and low tensile strength, therefore they cannot withstand the centrifugal force generated by high rotational speed (when using dovetail inserts). In order to guarantee the structural integrity, the PMs are usually encapsulated using retaining sleeves which pre-stress the material to compensate the centrifugal force at high speed operation [9]. This leads to two major drawbacks: firstly, the magnetic airgap becomes wider, with a consequent reduction of the average torque; secondly, depending on its composition, the sleeve can increase the total losses or can worsen the heat extraction from the rotor structure.…”
Section: Introductionmentioning
confidence: 99%
“…carbon fiber reinforced plastic). The former facilitate the heat removal from the rotor thanks to their superior thermal conductivity, but are prone to higher eddy current losses due to their good electrical conductivity; the latter show an enhanced weight to strength ratio but present opposite features in terms of thermal and electrical conductivity with respect to metallic sleeves [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in order to alleviate the energy shortage, energy conversion and energy storage engineering have been widely concerned. From nanoscale functional materials ( Ren et al, 2022a ; Zhang et al, 2022a ; Ren et al, 2022b ; Ren et al, 2022c ; Ren et al, 2022d ; Ren et al, 2022e ; Ren et al, 2022f ; Qin et al, 2022 ) to large engineering equipment ( Zhang et al, 2022b ; Lee and Hong, 2022 ; Li and Taghizadeh-Hesary, 2022 ), extensive energy conversion research studies have been developed. In recent years, compressed air energy storage has attracted significant focus ( Fayziyev et al, 2022 ; Liang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%